Effect of amitriptyline vs. physiotherapy in management of fibromyalgia syndrome: What predicts a clinical benefit? - Joshi M (Journal of Postgraduate Medicine, 2009)
Context : Fibromyalgia is a chronic disabling condition, and physicians treat it using a number of different treatment modalities. It is not known if one or more of such modalities are better than the others. We compared the efficacy of physiotherapy and amitriptyline in disability reduction in patients of fibromyalgia syndrome in a rural tertiary care hospital in Central India. Design : Open-label alternate patient treatment allocation. Materials and Methods : A six-month follow-up was done to assess the benefit of amitriptyline and physiotherapy for disability reduction in patients with fibromyalgia syndrome. Primary outcome measure was improvement in fibromyalgia impact questionnaire (FIQ) score. Statistical Analysis Used : Predictors of benefit were determined using multivariate logistic regression. Results : A total of 175 outpatients were assigned to either amitriptyline (n=87) or structured physiotherapy (n=88) treatments. There was a significant but similar (P=0.82) improvement in disability in both groups. High FIQ score at baseline and low socioeconomic status scores were significant predictors of benefit. Conclusions : Therapy with amitriptyline or physiotherapy is equally effective in improving outcome in patients of fibromyalgia over a period of six months.